2018
DOI: 10.1080/10717544.2018.1469687
|View full text |Cite
|
Sign up to set email alerts
|

Plateau hypoxia attenuates the metabolic activity of intestinal flora to enhance the bioavailability of nifedipine

Abstract: Nifedipine is completely absorbed by the gastrointestinal tract and its pharmacokinetics and metabolism may be influenced by microorganisms. If gut microbes are involved in the metabolism of nifedipine, plateau hypoxia may regulate the bioavailability and the therapeutic effect of nifedipine by altering the metabolic activity of the gut microbiota. We herein demonstrated for the first time that gut flora is involved in the metabolism of nifedipine by in vitro experiments. In addition, based on the results of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Hence, the diet greatly influences the diversity of the microbiota in the gut (Table 1). The microbiota is genetically well equipped to utilize various nutritional substrates [68] and maintains the normal gut microbiota pattern. A recent study has also shown that an increase in fat consumption generates a more gram-positive/gram-negative index of the gut microbiota [8].…”
Section: Interactions Between the Gut Microbiota And Dietary Nutrimentioning
confidence: 99%
“…Hence, the diet greatly influences the diversity of the microbiota in the gut (Table 1). The microbiota is genetically well equipped to utilize various nutritional substrates [68] and maintains the normal gut microbiota pattern. A recent study has also shown that an increase in fat consumption generates a more gram-positive/gram-negative index of the gut microbiota [8].…”
Section: Interactions Between the Gut Microbiota And Dietary Nutrimentioning
confidence: 99%
“…Fecal samples were sent to the BGI gene for 16S rRNA analysis in order to discover alterations in intestinal flora after rapidly ascent to high altitude. Cetyltrimethyl Ammonium Bromide (CTAB) method for extracting genomic DNA from fecal samples, followed by PCR analysis immediately [5]. We conducted bioinformatics analysis on qualified samples.…”
Section: S Rrna Analysismentioning
confidence: 99%
“…Aspirin and salicylic acid concentrations were analyzed using UFLC-MS / MS. High performance liquid chromatography (UFLC-20A, Shimadzu Corporation, Japan); Shim-pack XR-ODS column; Triple quadrupole mass spectrometer (API3200, Applied Biosystems, USA). The atomization temperature was 250˚C and the flow rate is 0.4 mL/min [5]. Electrospray ionization assay was used for in vitro incubation concentration of remaining aspirin and plasma concentration of salicylic acid in vivo.…”
Section: Uflc-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, high-altitude hypoxic conditions critically impact the individual's metabolite levels, vital enzymes, and metabolic pathways involved in in ammation and energy metabolism [3]. Besides, the intestinal micro ora also changes as a result of the major shift in the external atmospheric conditions at the same time [4].…”
Section: Introductionmentioning
confidence: 99%